A Proposed Training Program Based on the International Student Assessment Framework (PISA) to Develop the Teaching Practices of High School Mathematics Teachers and Its Impact on the Development of Productive Desire of their Students (Journal Of Educational and Psychological Researches, 2024)
The research aims to design a proposed training program based on the Program for International Student Assessment (PISA) and to investigate the program's impact on developing the teaching practices of mathematics teachers and the productive desire of their students in the first secondary grade. To achieve the research objectives, the researchers used the descriptive approach to develop a list of teaching practices within the framework of PISA, in addition to studying the training needs of teachers using the training needs questionnaire. The researchers also used the experimental approach for one group of teachers with two pre- and post-measurements using the observation card, as well as one group of students with two pre- and post-measurements using the productive desire scale. The samples consisted of 26 teachers, and 103 students were randomly chosen from the first secondary grade. The results showed a high training need for mathematics teachers to develop their teaching practices within the framework of PISA. The results also showed a positive impact of the training program on developing the teaching practices of mathematics teachers. Also, the results showed that there was no significant difference in the productive desire scale. In light of these results, some recommendations were made, including making use of the proposed training program within the framework of PISA to develop teaching practices for mathematics teachers and improve productive desire in mathematics among students.